2019
DOI: 10.1088/1361-648x/ab1b05
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and transverse magnetoresistance of SrTiO3with a single closed Fermi surface

Abstract: The magnetoresistance (MR) of SrTiO 3 is theoretically investigated based on the Boltzmann equation by considering its detailed band structure. The formula for MR proposed by Mackey and Sybert is extended to be applicable to a system with an arbitrarily shaped Fermi surface. It is shown that the angular dependence of the diagonal component of the mass tensor causes transverse MR, whereas that of the offdiagonal component causes longitudinal MR with only a single closed Fermi surface, which overturns the textbo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…This result suggests that the presence of the two-dimensional hollow Fermi surface, in which possible Dirac dispersion has been proposed, causes little influence on the emergence of a negative contribution. On the other hand, recent theoretical study showed that a negative magnetoresistance effect can arise from the warp of the Fermi surface from the perfect sphere, regardless of the nontrivial band topology [30]. Thus, more details of the Fermi surfaces in both CDW phase and normal metallic phase under high pressure are indispensable to discuss the origin of negative longitudinal magnetoresistance.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that the presence of the two-dimensional hollow Fermi surface, in which possible Dirac dispersion has been proposed, causes little influence on the emergence of a negative contribution. On the other hand, recent theoretical study showed that a negative magnetoresistance effect can arise from the warp of the Fermi surface from the perfect sphere, regardless of the nontrivial band topology [30]. Thus, more details of the Fermi surfaces in both CDW phase and normal metallic phase under high pressure are indispensable to discuss the origin of negative longitudinal magnetoresistance.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, there is a recent theoretical prediction, that a negative Gaussian curvature of the Fermi surface can cause a negative LMR [29].…”
Section: Possible Phenomena Causing a Magnetoresistancementioning
confidence: 98%
“…The linear magnetoresistance is expected to occur in the quantum limit state of a system having a linear energy dispersion [29] such as Dirac and Weyl semimetals. However, the power of magnetoresistance can be affected by disorder effects [30,31] and also the curvature of the relevant Fermi surface [32]. We also note that the data shown in Fig.…”
Section: Resultsmentioning
confidence: 60%